Diversity, characteristics, and abundance of native arbuscular mycorrhizal fungi in the semi-arid lands of Eastern Kenya - Sakha, Michael; Gweyi-Onyango, Joseph P.; Masso, Cargele; Baijukya, Frederick P. (Frontiers in Microbiology, 2025)
Elucidating the diversity of native arbuscular mycorrhizal (AM) fungi is essential for the sustainable management of semi-arid land ecosystems. This is because they significantly improve plant nutrient uptake and decrease the stress caused by biotic and abiotic factors. In this study, we examined the AM fungal communities and the key drivers influencing their diversity and occurrence in the smallholder farming systems of Eastern Kenya. Soils samples were collected from 34 diverse agricultural fields and AM fungal spores were extracted using wet-sieving and decantation techniques. The spores were quantified, and AM fungal communities were identified based on their morphological characteristics. Statistical data analyses, including relative abundance, the Shannon-Wiener index, analysis of variance (ANOVA), and principal component analysis (PCA), were performed using R software 4.4.0. The results revealed that two AM fungal families dominated the agricultural fields, namely Gigasporaceae (61.0%) and Acaulosporaceae (39.0%). These fungal families comprised a total of five genera, with the following relative abundances: Acaulospora (39.0%), Gigaspora (35.05%), Scutellospora (23.92%), Dentiscutata (1.32%), and Rococetra (0.72%). The AM fungal morpho-species were ranked from 1 to 26 across the five genera. Acaulospora denticulata ranked the highest, with a proportion of 25.19%. The Shannon-Wiener diversity index revealed a higher diversity of AM fungi in agricultural fields with greater spore richness. The PCA showed that the composition of AM fungal communities was strongly related to soil physiochemical characteristics. Dryland farming systems also played a role in AM fungal composition. Overall, the distribution of AM fungal communities across the agricultural fields was lower, implying the need to adopt sustainable dryland farming systems to enhance native AM fungal communities and support the development of context-specific biofertilizers.